Phubbing, Social Anxiety and Perceived Control in Young Adults - Rosemol Thamby; Shreelakshmi P (International Journal of Behavioral Sciences, 2025)
This study examines the complex interactions among ten empirical studies on social anxiety, phubbing (phone snubbing), and perceived control. Psychological research has focused a great deal of attention on social anxiety, which is characterized by the fear of being negatively evaluated in social situations. Phubbing, the practice of people prioritizing their phones over interpersonal interactions, has become more common in recent years due to the widespread use of smartphones. This behavior may exacerbate social anxiety, creating a cycle where individuals feel disconnected or judged during social interactions. Perceived control, or the personal conviction that one can affect results, has also been found to be an important component of anxiety management, influencing how individuals cope with stressful social situations. This integrative review clarifies the complex relationships between these constructs through a meta-synthesis approach along with semi-structured interviews with participants who experience social anxiety. By combining findings from multiple sources, the study aims to identify recurring patterns and underlying mechanisms that link phubbing, perceived control, and social anxiety. A total of ten peer-reviewed studies from 2000–2004 were selected for review from recognized peer-reviewed databases, including PubMed, PsycINFO, Scopus, and Web of Science. Meta-synthesis and thematic analysis were used for data analysis, allowing for a thorough examination of trends, commonalities, and key insights across studies, thus providing a comprehensive understanding of the interplay among social anxiety, phubbing, and perceived control
Keywords: Social anxiety; perceived control; phubbing; social interaction; social media